2008
DOI: 10.1177/1744987108090297
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the uptake and design of action research in published nursing research, 2000-2005

Abstract: Action research (AR) is promoted for health care development. A systematic review was undertaken to gain insight into the uptake and designs of practice-based AR. Empirical research papers from 2000 to 2005 were extracted from CINAHL, MEDLINE and British Nursing Index, and two specialist AR journals. The initial search identified 335 papers: 38% were AR (20% were phenomenology; 32% ethnography; 10% randomised-controlled trials). Further filtering produced 62 AR papers for detailed analysis. Eighty-seven per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…In their literature review, Munn-Giddings, McVicar, and Smith (2008) found that most of the methods employed in action research including PAR are participant observation, interviews and questionnaires. None of these methods is actionoriented, thus inappropriate to guide PAR cyclical process in order to achieve the personal and social transformation of the co-participants' practices and workplaces.…”
Section: Methodological and Philosophical Shortcomingsmentioning
confidence: 99%
“…In their literature review, Munn-Giddings, McVicar, and Smith (2008) found that most of the methods employed in action research including PAR are participant observation, interviews and questionnaires. None of these methods is actionoriented, thus inappropriate to guide PAR cyclical process in order to achieve the personal and social transformation of the co-participants' practices and workplaces.…”
Section: Methodological and Philosophical Shortcomingsmentioning
confidence: 99%
“…For example, Soh et al 87 reviewed action research studies in intensive care settings but of the 21 studies included only one described improved health-care outcomes. 88 Munn-Giddings et al 89 reviewed studies of action research in nursing published between 2000 and 2005. Munn-Giddings et al 89 identified 62 studies, but 'Only 13% could be defined as having their focus on a direct impact on patient care' (p. 474).…”
Section: Action Research and Participatory Action Researchmentioning
confidence: 99%
“…88 Munn-Giddings et al 89 reviewed studies of action research in nursing published between 2000 and 2005. Munn-Giddings et al 89 identified 62 studies, but 'Only 13% could be defined as having their focus on a direct impact on patient care' (p. 474).…”
Section: Action Research and Participatory Action Researchmentioning
confidence: 99%
“…As a healthcare discipline, nursing uses action research mainly in the hospital setting (Munn-Giddings et al, 2008), where it is conducive to solving clinical questions, because both the nursing process and action research assess, plan and implement ideas as part of a systematic approach, ultimately to problem solve issues . Hope and Waterman (2003) agree that the problem solving approach of action research "mirrors that of the nursing process" (p. 121).…”
Section: Action Research In Nursingmentioning
confidence: 99%